The Analysis of Risk Management Implementation in Laboratory Department of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Tengkeran, Nurul Ainun; Suleman, Juliko; Tilome, Efendi; Hatibie, Toar. W.J. (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Risk management is a program to reduce incidents of accidents that can be prevented to minimize financial losses to hospitals, moreover, risk management is done to prevent risks both small and large that can have an impact on a company. The current study aims to find out the process of implementing risk management in the laboratory department of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. This research used qualitative research methods involving a grounded theory approach. Grounded theory is a qualitative research method that uses several systematic procedures to find theories. The types of data used were primary data and secondary data were obtained from interviews and documentation. The results show that (1) Standard Operating Procedures (SPO) in laboratory installations are already existed and are effectively running, (2) The implementation of risk management has been regulated based on the regulation of Decree No. 12 of 2020 on Hospital Accreditation, (3) The skills of officers are in the forms of identifying risks in the laboratory. Furthermore, the implementation of risk management in laboratory installations has received a lot of support from hospital stakeholders.